UNIT 10.19 Digital Data Acquisition and Processing. Issue 1 (5th January 2015) - Naivar, Mark A.; Galbraith, David W.
Abstract : A flow cytometer is made up of many different subsystems that work together to measure the optical properties of individual cells within a sample. The data acquisition system (also called the data system) is one of these subsystems, and it is responsible for converting the electrical signals from the optical detectors into list‐mode data. This unit describes the inner workings of the data system, and provides insight into how the instrument functions as a whole. Some of the information provided in this unit is applicable to everyday use of these instruments, and, at minimum, should make it easier for the reader to assemble a specific data system. With the considerable advancement of electronics technology, it becomes possible to build an entirely functional data system using inexpensive hobbyist‐level electronics. This unit covers both analog and digital data systems, but the primary focus is on the more prevalent digital data systems of modern flow cytometric instrumentation. © 2015 by John Wiley & Sons, Inc.